ANALISIS PENGETAHUAN DAN SIKAP BIDAN TENTANG MANAJEMEN RISIKO PERSALINAN DAN IMPLEMENTASINYA - Marsheila Salvinia Amanitia Setiawan; Setiawandari, Setiawandari; Setiawandari, Solichatin (Rena Cipta Mandiri, 2025)
Labor risk management plays an essential role in preventing complications that may endanger mothers and newborns. This study aimed to analyze the relationship between midwives’ knowledge and attitudes toward the implementation of labor risk management at Independent Midwife Practices in the South Surabaya area. The research employed a quantitative cross-sectional design with a total sample of 25 certified “Bidan Delima” midwives. Data were collected using questionnaires and observation sheets, and analyzed using the Spearman correlation test. The results showed that 40% of midwives had moderate knowledge, 52% had good attitudes, and 44% implemented risk management effectively. There was a significant relationship between knowledge and implementation (p < 0.001; r = 0.693) as well as between attitude and implementation (p = 0.002; r = 0.582). Good knowledge and attitudes enhance the effective application of risk management. Regular training programs are needed for midwives to update their knowledge and skills in order to reduce maternal and neonatal mortality rates.